Collaborative problem based learning within social learning environment to enhance students' argumentative knowledge construction process in learning English literature - Khamis, Norzie (2013)
The purpose of this study is to investigate the influence of Collaborative Problem Based Learning (CPBL) within Social Learning Environment (SLE) to enhance secondary school students’ knowledge construction process in learning English Literature as higher order thinking skills is seen as vital aspect in education. In this 21st century, SLE can be seen as a suitable medium to encourage knowledge sharing, analysing information and exchanging opinions among the students and thus, nurture one’s knowledge construction process. The researcher started the study by developing CPBL learning materials based on PBL and Computer Supported Collaborative Learning (CSCL) principles to be integrated within SLE. This study involved three instruments; (1) online discussions scripts, (2) final writing assignment and (3) questionnaire. Qualitative data was gathered using thematic content analyses of 20 discussion scripts and final writings as to analyse the types of interaction occurred during the knowledge construction process and their argumentative skills using Toulmin’s Model. Then, interview was used to understand its influence on students’ argumentative skills. Finally, a survey was distributed as to examine students’ level of acceptance towards this approach. The results showed that cognitive contribution (74.85%) was the highest occurrences in the discussions scripts in which high-level elaborations (32.22%) were slightly lower than low-level elaborations (42.63%). This brings to low-level of argumentation skills in most of the final writing analyses. The content analyses on final writings showed students who interacted using high-level of elaborations during the discussions tend to provide high-level of Toulmin’s argumentation level in final writings. The ones who interacted using low-level interactions, albeit in small amount, also displayed encouraging argumentation skills in their final writings. Interview data indicated that CPBL had encouraged the students to jointly construct own knowledge, analyse each other’s reasoning and thus, enhance their argumentative skills. The finding further shows high level of acceptance towards this alternative medium of learning (M=4.21). Hence, collaborative learning supported by online learning is thus, possible to encourage students’ knowledge construction process. Educators then should organize a learning environment as to prompt such interaction to further encourage the development of higher order thinking skills amongst students